HYPERTHERMIC INTRAPERITONEAL CHEMOTHERAPY (HIPEC) IS AN EFFECTIVE METHOD OF TREATMENT FOR ABDOMINAL CAVITY CARCINOMATOSIS (LITERATURE REVIEW) (World Bulletin of Public Health, 2022)
One of the frequent options for the progression of malignant neoplasms of various localizations is carcinomatosis with tumor cells affecting the serous membranes - the peritoneum, omentum, parietal and / or visceral pleura, meninges of the brain. Peritoneal carcinomatosis, according to various sources, develops in at least 20-35% of patients with primary malignant tumors as a result of transcoelomic spread of tumor cells of intraabdominal organs. Intraperitoneal chemotherapy HIPEC is one of the highly effective methods of drug antitumor therapy, which involves the introduction of heated chemotherapy drugs into the tumor lesion. The technique provides the most complete destruction of cancer cells, increases the overall and relapse-free survival of cancer patients.
Keywords: Carcinomatosis; Intraperitoneal Chemotherapy; Hyperthermia